Early Hearing Preservation Outcomes Following Cochlear Implantation With New Slim Lateral Wall Electrode Using Electrocochleography. Issue 4 (16th April 2022) - Walia, Amit; Shew, Matthew A.; Ettyreddy, Abhinav; Lefler, Shannon M.; Jiramongkolchai, Pawina; Wick, Cameron C.; Durakovic, Nedim; Buchman, Craig A.; Herzog, Jacques A.
Abstract : Objective: Describe early hearing preservation (HP) cochlear implantation (CI) outcomes using a new slim lateral wall electrode (SLWE). Study Design: Prospective cohort study. Setting: Tertiary referral center. Patients: Adult CI candidates with preoperative low-frequency pure-tone average (LFPTA; 125, 250, 500 Hz) ≤60 dB HL. Intervention: CI with and without intracochlear real-time electrocochleography (RT-ECochG). Main Outcome Measure: HP (LFPTA ≤80 dB HL), LFPTA shift, speech-perception performance measures, postoperative CT reconstruction. Results: Forty-two subjects were implanted with the SLWE. Thirty patients underwent full insertion without RT-ECochG feedback, and HP was maintained at 3-months postactivation for 7 (23.3%) patients with mean LFPTA shift of 57.5 ± 25.6 dB HL. RT-ECochG feedback was utilized on 12 patients, of whom 6 patients had full insertions and 6 patients had anywhere from 1 to 3 electrodes left outside of the cochlea based on RT-ECochG feedback. At 3 months postoperatively, HP was achieved on 10 (83.3%) patients and mean LFPTA shift was 18.9 c 11.7 dB HL. Mean difference between LFPTA threshold shift at 3-months postactivation with and without RT-ECochG was 38.6 dB HL (95% CI, 25.6–51.67). There was an improvement in delta CNC from preoperative to 3-months postactivation when using RT-ECochG, with mean difference 20.7% (95% CI, 3.3–38.1). Conclusions: Use of RT-ECochG monitoring during SLWE placement results in fewer full electrode insertions and significantly better HP rates and speech-perception outcomes when compared with unmonitored insertions. Further investigation is needed to evaluate long-term audiologic outcomes to better understand the relationships among ECochG, cochlear trauma, functional outcomes, and HP.